Genetic variation between wild type and auxotrophic mutant isolates of Sinorhizobium meliloti by using RAPDPCR technique - Hussein, Ihsan A.; Ganim, Salwa A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
SGI2 wild type isolate of Sinorhizobium meliloti was isolated from Medicago sativa (alfalfa) plant which was obtained from Al-Tarmiaa region / Baghdad. Nine auxotrophic mutants were obtained from the SGI2 wild type isolate by mutagenesis with Nitrous acid (HNO2). The SGI2 wild type and the all auxotrophic mutant isolates had two Megaplasmids; pSymA and pSymB. No genetic variations in plasmid number and size were detected when gel electrophoresis was done for plasmid profile detection. Genetic variations by using RAPD-PCR technique were obtained between wild type and auxotrophic mutant isolates. One band was detected in SGI6 gel profile with 1.5 Kb size when OPY-04 primer was used. Using OPB7 primer by using RAPD-PCR technique showed large variation between all the isolates. Two bands were obtained from the SGI2 wild type isolate with 800 bases and 1.5 Kb in size. These bands were absent from the auxotrophic mutant isolates. The band with 800 bases was also found in SGI10 isolate. The other auxotrophic mutant isolates have different bands with size ranging from 200 bases and more than 1.5 Kb for the SGI6 isolate. No bands were detected in SGI8, SGI9 and SG12 isolates. The large differences in bands number and size suggested that the variation is clear at the genes level of the total genome and not at plasmid level as a result after nitrous acid mutagenesis.